Assessment of Periodontal Health in Patients with Alzheimer's disease in Karachi, Pakistan: Periodontal Health in Alzheimer's Patients - Mushtaque, Ujala; Khan, Muhammad Ibtahaj; Tariq, Rohan; Rijah, Syeda; Zaidi, Hibba Batool; Aslam, Abdullah (Pakistan Journal of Health Sciences, 2025)
Alzheimer's disease (AD), causes permanent loss of neurons and neural connections. Objective: To assess the periodontal health status of Alzheimer's disease (AD) patients by assessing plaque index, gingival condition, probing pocket depth, attachment levels, and bleeding on probing, and to correlate these findings with cognitive impairment levels as determined by Mini-Mental State Examination (MMSE) scores. Methods: A cross-sectional study, was conducted at Medicare Hospital between July and October 2024. Total 60 patients were recruited in the study. Hence plaque index, gingival condition, probing depth, attachment levels, and bleeding on probing were used to assess periodontal health, whereas MMSE scores were used to classify cognitive impairment. For statistical analysis, ANOVA and unpaired t-test analyses are carried out using SPSS version 24.0. All of the findings were deemed statistically significant if P was less than 0.05. Results: The study results revealed that the demographic and neurological parameters such as age, the distribution of genders, and the number of teeth of those patients suffering from Alzheimer’s disease. Hence, MMSE scores were significantly lower, indicating substantial cognitive impairment (P < 0.001). As the severity of AD increases, there is a trend for all recorded variables to get worse (p < 0.01). PPD and CAL reveal more periodontal tissue loss in patients with severe AD, while PI and GI show more plaque accumulation and gingival inflammation. Conclusions: This study highlighted a strong link between worsening periodontal health and Alzheimer's severity, emphasizing the need for proactive dental care to improve patient well-being.